2020
DOI: 10.1007/s11666-020-01112-8
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic Phase Evolution of Cold-Sprayed Ni-Ti Composite Coatings: Influence of As-Sprayed Chemical Composition

Abstract: Owing to low-temperature deposition conditions and high deposition rate, cold spray offers unique advantages in manufacturing a wide variety of metallic and composite coatings including metal matrix composites produced from physically blended powders. One of the challenges of producing composite coatings using cold spray is the deviation of coatings composition from the blended feedstock powder composition. This is of utmost importance as it affects the composition and phase evolution of intermetallic forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…12 shows the cross sectional micrograph of the worn Cp Ti under an applied load of 40 N. It can be seen that holes and cracks are formed in depth below the surface and eventually result in the formation of debris with a possible delamination mechanism. In fact, by increasing the amount of the applied force, the surface temperature increases due to the heat generated by friction, and as stated in a previous research [26], the yield strength of titanium decreases by increasing temperature and as a consequence, the plastic deformation becomes more severe. Briefly, even under a high load (40N),…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…12 shows the cross sectional micrograph of the worn Cp Ti under an applied load of 40 N. It can be seen that holes and cracks are formed in depth below the surface and eventually result in the formation of debris with a possible delamination mechanism. In fact, by increasing the amount of the applied force, the surface temperature increases due to the heat generated by friction, and as stated in a previous research [26], the yield strength of titanium decreases by increasing temperature and as a consequence, the plastic deformation becomes more severe. Briefly, even under a high load (40N),…”
Section: Resultsmentioning
confidence: 59%
“…Therefore, applying a diffusion-based treatment, which improves adhesion strength to the substrate, can overcome the defects of the previous methods [25]. Nikbakht et al [26] reported the formation of a composite Ni-Ti coating on the titanium substrate through a cold spray method followed by a heat treatment. Li et al [27,28] proposed a new method for preparing Ni-Ti intermetallic compounds by nickel plating on titanium substrate followed by electron beam remelting.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the CS process in the production of metal matrix composite (MMC) material is the low working temperature, which eliminates oxidation and possible matrix-reinforcement (ceramic, metallic, or intermetallic) interfacial reactions, thus preserving the feedstock material microstructure (Ref 379 ). CS deposition of MMC can be divided into two main categories based on the nature of the reinforcement materials: metal-metal MMCs and ceramic-metal MMCs.…”
Section: Cold Spray Application Pillars (Past Present and Future)mentioning
confidence: 99%
“…Such coatings are used as wear-resistant and corrosionresistant barriers in different domains of industry [1,2]. In some cases, the metal composite coatings are used as the precursors for following heat treatment [3][4][5][6]. Due to the chemical reaction between the coating components during heat treatment, the new phases with unique properties could be formed.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the coating is obtained by simultaneous spraying of several low-cost commercially available pure metal or alloy powders. Nowadays the articles devoted to thermal spraying of metal powder mixtures are available [3][4][5][6]11]. However, the main issue limiting the application of thermal spray methods for elaboration of metal composites using the powder blends is the complexity of simultaneous spraying of powders with different thermal properties.…”
Section: Introductionmentioning
confidence: 99%